2021
DOI: 10.3390/healthcare9121677
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of People with Dementia and Informal Carers Related to the Closure of Social and Medical Services in Poland during the COVID-19 Pandemic—A Qualitative Study

Abstract: Older people with dementia are particularly at risk of COVID-19; however, relatively little is known about the indirect impact of the pandemic on the lives of those living with, and/or caring for someone with, dementia. The aim of this study was to investigate the experiences of people with dementia and informal carers during the closure of available social and medical services in Poland during the COVID-19 pandemic. A qualitative thematic analysis of semi-structured interviews with people with dementia (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 72 publications
1
28
1
Order By: Relevance
“…Such findings were also reported in many other countries worldwide (Suárez-González et al, 2021) and partially relate to reported higher levels of anxiety and depression among older Australians compared with pre-COVID-19 (Strutt et al, 2022). Our findings did not highlight positive aspects of providing informal care for people living with dementia, such as spending more time together, which were reported by carers in other countries and in an Australian study focusing on positive experiences and coping strategies (Maćkowiak et al, 2021; Tulloch et al, 2021). This aspect should be explored in further studies.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Such findings were also reported in many other countries worldwide (Suárez-González et al, 2021) and partially relate to reported higher levels of anxiety and depression among older Australians compared with pre-COVID-19 (Strutt et al, 2022). Our findings did not highlight positive aspects of providing informal care for people living with dementia, such as spending more time together, which were reported by carers in other countries and in an Australian study focusing on positive experiences and coping strategies (Maćkowiak et al, 2021; Tulloch et al, 2021). This aspect should be explored in further studies.…”
Section: Discussioncontrasting
confidence: 98%
“…The increased burden of care was quite often caused by additional changes related to the pandemic, such as home-learning and working from home. This increased burden of care was observed internationally in countries like the United Kingdom, Canada, and Poland Losada et al, 2022;Maćkowiak et al, 2021), and especially among women (Eurocarers/IRCCS-INRCA, 2021;Power, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…38,39 Social distancing rules imposed by the pandemic interrupted access to routine healthcare for those vulnerable people at an increased risk of virus infection, morbidity and mortality. In such a context, evidence on the use of technology in healthcare emerged in Poland and in Australia 40,41 only. However, based on our findings, difficulties with remote healthcare arose, and teleconsultations, specifically, seem not to work for people with dementia who prefer physical contact and rely on non-verbal communication, especially when their cognition is seriously compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported the lock-down restrictions from COVID-19 caused PLWDs to feel a lack of motivation and a reduction in cognitive abilities to maintain daily activities. The added requirements of maintaining social distancing and cessation of daily outdoor activities have caused a reduction in physical activity, social participation, and a lack of cognitive stimulation[ 13 15 ]. The COVID-19 pandemic has widened the differences between existing care methods and typical challenges and difficulties experienced by FCGs, which has led to increased caregiver burden related to practical difficulties, emotional stress, and difficulty asking for help [ 11 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 restrictions have generated unprecedented challenges for FCGs and PLWDs, especially in the reorganization of their daily routine and care relationships [ 13 ]. These caregivers have multiple needs which are more difficult to address during restrictions of the COVID-19 pandemic, which may need what Rokstadt et al (2021) refer to as “radical changes” in services, such as a greater availability of telemedicine for consultations with dementia specialists and social support services either via video- or telephone-based services [ 17 ].…”
Section: Introductionmentioning
confidence: 99%